Modelo Europeo de Gestión de Calidad TotalFoundation European for Quality of Management EFQM: ¿Asegurar la calidad de las Instituciones de Educación Superior a través de Sistemas de Gestión de Calidad, conlleva a un cambio de cultura? (Boletín de Políticas y Gestión Educativa, 2022)
The EFQM model of the European Foundation for Quality Management and Excellence is a management system based in Brussels that offers companies and private and public institutions a self-assessment process to determine improvement processes that will lead them to create an sustainable future, develop the capacity of the organization, take advantage of creativity and innovation, have leadership that has vision, inspiration and integrity and can manage and achieve organizational success through the talent of people and maintain excellent results that remain in the time. To achieve this, it is essential to have a collaborative organization willing to constantly learn and transform in order to adapt to the changes, needs and demands of the environment. It should be noted that the organization corresponds to people who are part of the collective, a whole that represents much more than the sum of the parts.
Keywords: Model, management system, quality, excellence, improvement processes, leadership, collaborative organization, people and collective